The Corridor as a Main Axis in The Tasripin Heritage House, Kampung Kulitan: a Space Syntax Study - Yusuf Muslim; Bangun I. R. Harsritanto (Sinektika: Jurnal Arsitektur, 2026)
The Tasripin Heritage House in Kampung Kulitan, Semarang, represents one of the few surviving examples of traditional Javanese spatial continuity within an urban setting. However, increasing urban densification and physical transformations threaten the legibility of its traditional spatial configuration, particularly the role of the corridor as a transitional connector. This study aims to analyze the spatial configuration of the house, with an emphasis on the functional role of the corridor as the axial connector between spaces. The research employs a spatial configuration analysis using Space Syntax through DepthmapX software. Data were collected through field surveys, architectural documentation, and redrawn floor plans. Axial and convex map analyses were conducted to measure the degree of integration and spatial connectivity. The results reveal that the corridor has the highest integration value, confirming its role as the main transitional axis between public, semi-public, and private zones. The study concludes that the corridor in Javanese heritage houses in Kampung Kulitan functions not only as a circulation element but also as a spatial identity that symbolizes the main axis and the balance between social openness and domestic privacy. This research contributes to the understanding of traditional spatial configuration preservation within the context of urban vernacular architecture.